Penerapan Metode Pembelajaran Kooperatif untuk Meningkatkan Pemahaman Konsep Matematika di MIS Hidayatul Islamiyah - Rojiah , Siti; Rodiah, Siti; Qoriah , Siti Nur (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of the cooperative learning method in improving students’ understanding of mathematical concepts at MIS Hidayatul Islamiyah. This research adopts a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 27 fifth-grade students. Data collection techniques included concept comprehension tests, observations, and documentation. The results showed that the cooperative learning method significantly improved students’ understanding of mathematical concepts. In the first cycle, the average student comprehension score was 65, while in the second cycle, it increased to 80. This improvement indicates that the cooperative learning method effectively encourages active student engagement and enhances their understanding of mathematical concepts. Therefore, this method is recommended for implementation in elementary school mathematics learning.